A novel distinctive form of identification for differential diagnosis of irritable bowel syndrome, inflammatory bowel disease, and healthy controls. Issue 5 (27th August 2020) - Ramió‐Pujol, Sara; Amoedo, Joan; Serra‐Pagès, Mariona; Torrealba, Leyanira; Bahí, Anna; Serrano, Marta; Malagón, Marta; Ibáñez‐Sanz, Gemma; Gilabert, Pau; Marin, Ingrid; Torres, Paola; Cañete, Fiorella; et al.
Abstract: Background: Irritable bowel syndrome (IBS) is a functional disorder affecting around 11% of the world population, which diagnostic is mainly based on clinical parameters. IBS shares many symptoms with other gastrointestinal disorders such as inflammatory bowel disease (IBD), which makes positive diagnosis a difficult task. Aim: This work presents the design of a new test, called RAID‐Dx, which is a mathematical algorithm based on the combination of nine faecal microbial markers capable of diagnosing IBS. Methods: A cohort consisting of 165 subjects (52 IBS and 52 IBD patients, and 61 healthy controls) was recruited from the Gastroenterology Department of six hospitals. Each patient provided a stool sample from which DNA was extracted, and microbial markers composing RAID‐Dx were analysed by qPCR. The results obtained were used to define and validate the RAID‐Dx algorithm. Results: The abundance of the biomarkers included in the algorithm differed according to the diagnosis. RAID‐Dx shows a high capacity to diagnose IBS with a sensitivity of 82.4% and a specificity of 85.7%. RAID‐Dx also reports higher sensitivity and specificity values than faecal calprotectin for IBS and IBD differentiation. Conclusions: RAID‐Dx is a noninvasive tool aimed to diagnose IBS with high sensitivity and specificity. The use of this new tool for IBS diagnosis could significantly improve disease management, minimise its misdiagnosis and increase patients' quality of life.